AI in School Governance: Efficiency or Dehumanization of Education? - Beni Kurniawan; Mustiali; Jasmansyah; Rasyid Ridlo (WISE Pendidikan Indonesia, 2026)
This study aims to explore the lived experiences of educational stakeholders in interpreting the implementation of artificial intelligence (AI) in school governance. Employing a qualitative approach with Husserl's descriptive phenomenological design, this study involved 15 participants consisting of a principal, vice principal, school supervisor, senior and junior teachers, school operator, administrative staff, a student, and a parent. Data were collected through semi-structured in-depth interviews and analyzed using a modified Stevick-Colaizzi-Keen method. The findings identified five major phenomenological themes: (1) administrative efficiency as a transformative experience, (2) relational dehumanization within the school ecosystem, (3) digital pressure and institutional surveillance, (4) intergenerational adaptation gaps, and (5) the dialectic of hope between technology and humanism. Results demonstrate that AI creates an efficiency-dehumanization paradox: it accelerates administrative processes while simultaneously eroding interpersonal relationships and transforming the essence of education into mechanistic practices. This study concludes that a human-centered AI governance framework is needed to maintain the balance between technological efficiency and humanistic educational values.